Clinical and echographic features of in utero cardiac dysfunction in the recipient twin in twin-twin transfusion syndrome. Issue 1 (July 1994) - Zosmer, N; Bajoria, R; Weiner, E; Rigby, M; Vaughan, J; Fisk, N M
Abstract : OBJECTIVE--Fetal twin-twin transfusion syndrome (TTTS) presenting in the second trimester has been associated with almost no perinatal survival until recently, when serial drainage of amniotic fluid has improved the prognosis to 70%-80%. Most recipient twins now survive but develop cardiac dysfunction. The study was undertaken to evaluate the abnormal echocardiographic features and clinical complications of cardiac disease in the recipient twin of TTTS. DESIGN--Antenatal and postnatal echocardiographic and clinical observational study. SETTING--Antenatal studies in a tertiary referral centre. Postnatal management and follow up were performed by the same paediatric cardiologist, either at the obstetric hospital or at the regional referral centre. PATIENTS--Twin pregnancies complicated by TTTS with severe polyhydramnios diagnosed earlier than 25 weeks that proceeded until viability (n = 5). INTERVENTION--Serial fetal echocardiography with colour Doppler. Postnatal echocardiography in the first week and between two and seven months. Serial amnioreduction was performed in all pregnancies. Digoxin treatment, pericardiocentesis, paracentesis, or laser ablation of placental anastomoses was undertaken when there was hydrops. RESULTS--Increased cardiothoracic ratio and tricuspid regurgitation were seen in all recipient twins. High pulmonary artery velocities developed in three. One recipient twin died a week after delivery of endocardial fibroelastosis and infundibular pulmonary stenosis. Two other had balloon dilatation for pulmonary stenosis, one shortly after birth and one at four months. A further twin has apical thickening of the right ventricle at six months. The remaining recipient twin had normal echocardiographic findings at follow up. CONCLUSION--This report characterises for the first time a cardiac disease acquired in utero in the recipient twin in pregnancies complicated by TTTS. Clinical manifestations in utero range from mild to critical pulmonary stenosis or lethal cardiomyopathy. Although perinatal prognosis seems to be related to the severity of dysfunction when first diagnosed in utero, follow up in infancy is recommended in view of the possibility of progressive pulmonary stenosis.